The study of clinico-pathological correlation and treatment outcome in acute allograft rejection in the immediate post renal transplant period - Beigh, Aadil; Gupta, Bheem Raj; Sagar, Gaurav; Agarwal, D. K. (International Journal of Research in Medical Sciences, 2019)
Background: The kidney Tx is the treatment of choice for patients with ESRD. However, episodes of AR have a negative impact on short- and long-term graft survival. In spite of immunosuppressive medications, CNI, MMF and steroid, the AR remains a crucial problem for Tx. This analysis was performed to evaluate the changing profile of early AR (during first week of transplant) and its repercussions on graft survival. Methods: This study was an observational cohort study and included 50 renal transplant patients irrespective of age, sex and race who developed bx proven AR within first week of transplant. Three groups were made according to histopathology: ACR, AMR and mixed rejection group. The patients were followed for 6 months thereafter. Results: AR within a week of renal Tx were less symptomatic except decrease in UO. ACR was more common (72%) than AMR and mixed rejections. AMR and Mixed group required more therapeutic modalities than ACR. More patients required HD during AR in AMR and mixed rejection group than ACR. The mean s.cr at 6 months was 1.3,1.5 and 1.6 in ACR, AMR and mixed group respectively. There were more incidences of BK viremia, CMV infection UTI and rejection fronts follow up in AMR and mixed group than ACR group. Conclusions: Acute rejections within a week are less symptomatic and ACR occurred more frequently than AMR and mixed rejection There were more incidences of BKV, CMV and UTI for 6 months follow up in AMR and Mixed rejection group.